Endobronchial laser ablation in the management of epithelial-myoepithelial carcinoma of the trachea. (2015) - McCracken, David; Wieboldt, Jason; Sidhu, Pushpinder; McManus, Kieran
Abstract: A 52 year old, never smoker presented to hospital with progressive shortness of breath and significant stridor over a five month period. He also described the feeling of needing to cough but being unable to expectorate. CT Thorax demonstrated a mass lesion in the trachea just distal to the larynx which was then confirmed on rigid bronchoscopy. Subsequent histology confirmed an epithelial-myoepithelial carcinoma. Only a few case reports document these rare salivary gland tumours occurring in other locations such as the respiratory tract. After staging showed only local disease, the patient was managed with rigid bronchoscopy and laser ablation therapy. We present the first documented case to be treated with endobronchial laser ablation therapy with discussion of the incidence, presentation and characteristics of these tumours including the treatment options, as well as the use of laser ablation in the management of benign and malignant endobronchial lesions.